The emerging role of Artificial Intelligence in proton therapy: A review - Isaksson, Lars Johannes; Mastroleo, Federico; Vincini, Maria Giulia; Marvaso, Giulia; Zaffaroni, Mattia; Gola, Michał; Mazzola, Giovanni Carlo; Bergamaschi, Luca; Gaito, Simona; Alongi, Filippo; Doyen, Jerome; Fossati, Piero; et al. (Critical reviews in oncology/hematology, 2024)
Artificial intelligence (AI) has made a tremendous impact in the space of healthcare, and proton therapy is not an exception. Proton therapy has witnessed growing popularity in oncology over recent decades, and researchers are increasingly looking to develop AI and machine learning tools to aid in various steps of the treatment planning and delivery processes. This review delves into the emergent role of AI in proton therapy, evaluating its development, advantages, intended clinical contexts, and areas of application. Through the analysis of 76 studies, we aim to underscore the importance of AI applications in advancing proton therapy and to highlight their prospective influence on clinical practices.
Keywords: Neoplasms; nádory; strojové učení; Artificial intelligence; lidé; umělá inteligence; Proton Therapy; Radiotherapy Planning, Computer-Assisted; Review; plánování radioterapie pomocí počítače; protonová terapie; Artificial Intelligence; Machine Learning; Proton therapy; Humans